Neurotoxicity with persistent unilateral ophthalmoplegia from envenoming by a wild inland taipan (Oxyuranus microlepidotus, Elapidae) in remote outback South Australia. (October 2017) - Weinstein, Scott A.; Everest, Evan; Purdell-Lewis, Jeremy; Harrison, Michael; Tavender, Fiona; Alfred, Sam; Marrack, Liz; Davenport-Klunder, Chris; Wearn, Neralie; White, Julian
Abstract: Introduction: A case of life threatening envenoming by a wild specimen of the inland taipan, Oxyuranus microlepidotus, is described. There have been 11 previously well-documented envenomings by O. microlepidotus, but only 2 were inflicted by wild snakes. Envenomed patients have presented predominantly with defibrinating coagulopathy and neurotoxicity. Case report: The victim was seeking to observe members of an isolated population of this species and was envenomed while attempting to photograph an approximately 1.5 m specimen. He reported feeling "drowsiness" and blurred vision that progressed to ptosis; he later developed dysphagia and dysarthria. The patient was treated with 1 vial of polyvalent antivenom, which was later followed with an additional two vials of taipan monovalent. He was intubated during retrieval, and recovered after 3 days of intensive care. He had a right ophthalmoplegia that persisted for approximately 1 week post-envenoming. Despite a positive 20-min whole blood clotting test, defibrination coagulopathy was absent, and there was no myotoxicity, or acute kidney injury. Discussion: Physicians presented with a patient envenomed by O. microlepidotus should remain cognizant of the possible variability of medically important venom toxins in some populations of this species. Some patients seriously envenomed by this species may develop persistent cranial nerve palsies. When clinically indicated, prompt provision of adequate antivenom is the cornerstone of managing O. microlepidotus envenoming. Rapid application of pressure-bandage immobilization and efficient retrieval of victims envenomed in remote locales, preferably by medically well-equipped aircraft, probably improves the likelihood of a positive outcome. Highlights: Documentation of a serious envenoming by a wild inland taipan ( Oxyuranus microlepidotus ) in the remote Australian outback. Defibrinating coagulopathy was absent; 20WBCTwas possibly a false positive or a transient anti-coagulant coagulopathy. The patient developed progressive neurotoxicity, was retrieved from outback; treated with Polyvalent and Taipan antivenom. Initial bilateral ophthalmoplegia notably pronouncedon the right side, persisted as unilateral right sided ophthalmoplegia. Full recovery achieved after 1 week.